"If my Plan Doesn't Work, I'll Follow the Doctor's Orders." A Dialogical Self Analysis of Chronic Patients' Medical Treatment Ambivalence. Issue 2 (26th April 2022) - Herrera, Pablo A.
Abstract: A patient's ambivalence toward medical and psychotherapeutic treatment is a strong predictor of its outcome. This is especially relevant in the treatment of common chronic conditions such as hypertension (HT), in which most patients do not maintain the lifestyle changes that lie at the heart of the medical treatment. Despite the growing theoretical interest, there is little empirical research on how patients deal with and resolve their ambivalence, and almost all of the studies focus on psychotherapy clients, not on chronic illness patients. This study aims to understand how patients with AHT deal with their ambivalence toward their medical treatment, using dialogical self-theory and qualitative research methods. We interviewed 51 hypertensive patients to identify their anti and pro adherence "voices" and the different strategies patients use for dealing with their ambivalence. Results describe integration strategies, which allow both opposing voices to express themselves and be heard, and domination strategies which reject or dismiss one of the voices. The temporal dynamics between PRO and ANTI adherence voices during the interviews are also explored. These results are discussed to contribute to the research on ambivalence and support concrete guidelines for dealing with patient nonadherence.